Aseguramiento de la calidad y competencia técnica en un laboratorio clínico basado en la NTC/ISO 15189:2014 (2021)
Clinical laboratories that adopt a quality management system based on the NTC / ISO 15189: 2014 present different challenges, success in achieving these challenges requires the skills and commitment of all staff to fulfill tasks, improve quality and achievement of objectives. An effective quality management system implementation plan in accordance with the standard is based on continuous improvement, reduction of errors and risk factors, to guarantee the correct execution in the provision of the diagnostic support service, with a view to obtaining recognition for its quality processes and good operational performance, towards patient safety. The diagnosis of the management system in a clinical laboratory under the requirements of the NTC-ISO 15189: 2014 standard, shows the different shortcomings that arise, such as document control, technical requirements, and quality assurance, being among the most frequent that clinical laboratories fail. The implementation of a quality management system with the objective of accreditation, based on the standard, demonstrates the improvement of quality and improvement of competence in the laboratory, reducing errors in the process, based on commitment, great leadership and a comprehensive action plan towards patient safety and satisfaction of all those involved to obtain an accurate diagnosis.